OCT1 genetic variants are associated with postoperative morphine-related adverse effects in children. (May 2017) - Balyan, Rajiv; Zhang, Xue; Chidambaran, Vidya; Martin, Lisa J; Mizuno, Tomoyuki; Fukuda, Tsuyoshi; Vinks, Alexander A; Sadhasivam, Senthilkumar
Aim: Large interindividual variability in morphine pharmacokinetics (PK) could contribute to variability in morphine analgesia and adverse events. Respiratory depression (RD) and postoperative nausea and vomiting (PONV) are significant adverse drug response of intravenous morphine in the perioperative setting limiting its efficacy in achieving adequate surgical pain relief. OCT1 is a transporter in the liver that transports morphine from the bloodstream into hepatocytes. Earlier we reported association of genetic polymorphisms in OCT1 with morphine PK, and lower morphine clearance in Caucasian children as compared with African–American (AA) children. The aim of this study is to identify the association between common OCT1 genotypes affecting morphine's PK and clinically important postoperative morphine-related adverse outcomes.Methods: After obtaining institutional review board (IRB) approval and informed consents, 311 children ages 6–15 years, American Society of Anesthesiologists' physical status 1 or 2 scheduled for tonsillectomy who received standard anesthetic, surgical and postoperative care were recruited. Clinical data collected included postoperative pain scores, total opioid use, incidence of PONV and RD. Four nonsynonymous SNPs of the OCT1 gene (rs12208357, rs34130495, rs72552763 and rs34059508) in each patient were genotyped using commercially available TaqMan assays. We investigated the genetic association of OCT1 with incidences of postoperative RD and PONV.Results: Caucasian and AA children differed significantly in the incidence of obstructive sleep apnea (p < 0.001) and total morphine use (p = 0.028). There were incidences of prolonged post anesthesia care unit stay in 7% of Caucasian children, while no such incidences were observed for AA children (p = 0.05). OCT1 polymorphism rs12208357 was associated with high incidences of PONV and PONV leading to prolonged post anesthesia care unit stay (p < 0.05). A significant association was also found between rs72552763 GAT deletion and high incidence of RD (p = 0.007).Conclusion: Children with certain OCT1 genotypes are associated with higher risk for RD and PONV following morphine administration leading to prolonged hospital stay. The OCT1 transporters' effects on morphine's PK could explain this association.